FAKTOR GAYA HIDUP YANG BERHUBUNGAN DENGAN PENYAKIT GASTRITIS DI WILAYAH KERJA PUSKESMAS SUNGAI DAREH - astuti ardi putri (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2021)
Lifestyle is characterized by behavioral patterns that have an impact on health, such as poor diet, smoking, and alcohol, and irregular eating patterns lead to digestive disease, namely gastritis. The purpose of the study was to obtain results about the relationship between diet, type of food, and cigarettes with the incidence of gastritis. This research used a descriptive method with a cross-sectional study. The number of samples carried out by the study was 50 respondents. The results showed that most of the 26 respondents (52.0%) with a poor diet; most of the respondents (52.0%) had poor eating and drinking habits; almost all respondents (76.0%) smoked; most of the respondents (58.0%) had gastritis. It can be concluded that there is a relationship between eating patterns, eating and drinking habits, and smoking on the incidence of gastritis. It is expected that respondents can maintain their diet and not smoke to prevent gastritis.